Austerity policing: Is visibility more important than absolute numbers in determining public confidence in the police?. (March 2013) - Sindall, Katy; Sturgis, Patrick
The recent deep cuts to police force budgets in the United Kingdom have reawakened longstanding debates about the effect of police numbers and organization on the crime rate and public confidence in the police. Whereas some claim that a reduction in numbers is likely to have a deleterious effect, others argue that raw numbers are less important than how the police are organized and deployed. By cutting red tape and focusing staffing reductions on 'back-office' functions, the argument goes, it should be possible to maintain a consistent 'frontline' presence, which is a key aspect of policing for maintaining citizen confidence in the service. In this article we use administrative data linked to the British Crime Survey in order to assess the relative importance of police numbers and police visibility in determining public confidence in the police. We find, as expected, that visibility has a significant and positive effect on confidence. However, we also find a significant and positive effect of police numbers over and above the effect of visibility. Moreover, because the extent to which police are visible in local areas is itself a function of the number of police employed, we find that the number of police has an additional indirect influence on public confidence through its direct effect on visibility. By implication, reducing police numbers is likely to erode public confidence in the police, even if frontline visibility is maintained through organizational efficiency.